Α‐Syntrophin alleviates ER stress to maintain protein homeostasis during myoblast differentiation. Issue 12 (22nd April 2021) - Moon, Jae Yun; Kim, Hye Sun
Abstract : We have previously shown evidence that α‐syntrophin plays an important role in myoblast differentiation. In this study, we focused on abnormal myotube formation of the α‐syntrophin knockdown C2 cell line (SNKD). The overall amount of intracellular protein and muscle‐specific proteins in SNKD cells were significantly lower than those in the control. Akt‐mTOR signaling, an important pathway for protein synthesis and muscle hypertrophy, was downregulated. In addition, the levels of endoplasmic reticulum (ER) stress markers increased in SNKD cells. The decrease in intracellular protein synthesis and reduction in the myotube diameter in SNKD cells were restored by 4‐phenylbutyric acid, a chemical chaperone, or overexpression of α‐syntrophin. These results suggest a novel role for α‐syntrophin in protein homeostasis during myoblast differentiation.